Literasi Digital dan Kewaspadaan Siber: Analisis Tingkat Kesadaran Privasi Pengguna Terhadap Ancaman Doxing - Nur Azizah; Bambang Mudjiyanto; Fit Yanuar; Nursyamsi Nursyamsi; Launa Launa (Jurnal Ilmu Komunikasi AKRAB, 2026)
Doxing—the forced disclosure of personal data in the digital realm—is currently aserious threat to social media users, especially young people who lack a clear understanding ofdigital security risks. This qualitative study, using a descriptive-interpretive approach, revealsthat privacy awareness and digital literacy among users remain low, while state protectionefforts are less than optimal. The study’s findings indicate that preventing doxing requires strongpolitical will, proactive public policies, and multi-stakeholder collaboration. Digital literacy isnot merely a technical necessity, but a fundamental right of citizens in a safe, ethical, andinclusive digital ecosystem. Strengthening literacy and privacy protection are essentialfoundations for a responsible digital society to support the growth of a sustainable digitalecosystem.Keywords: Doxing, cybercrime, privacy awareness, digital literacy, social media.